A Robust Seven-Gene Signature Associated With Tumor Microenvironment to Predict Survival Outcomes of Patients With Stage III–IV Lung Adenocarcinoma - Zhao, Hao; Zhang, Xuening; Guo, Lan; Shi, Songhe; Lu, Ciyong (Frontiers in Genetics, 2021)
Background: Due to the relatively insidious early symptoms of lung adenocarcinoma (LUAD), most LUAD patients are at an advanced stage at the time of diagnosis and lose the best chance of surgical resection. Mounting evidence suggested that the tumor microenvironment (TME) was highly correlated with tumor occurrence, progress, and prognosis. However, TME in advanced LUAD remained to be studied and reliable prognostic signatures based on TME in advanced LUAD also had not been well-established. This study aimed to understand the cell composition and function of TME and construct a gene signature associated with TME in advanced LUAD. Methods: The immune, stromal and estimate scores of each sample from the TCGA database were respectively calculated using an ESTIMATE algorithm. The LASSO and Cox regression model were applied to select prognostic genes and to construct a gene signature associated with TME. Two independent datasets from GEO were used for external validation. Twenty-two subsets of tumor-infiltrating immune cells (Tiics) were analyzed using the Cibersort algorithm. Results: Favorable overall survivals (OS) and progression-free survival (PFS) were found in patients with high immune score (P=0.048, P=0.028; respectively) and stromal score (P=0.024, P=0.025; respectively). Based on the immune and stromal scores, 453 differentially expressed genes (DEGs) were identified. Using the LASSO and Cox regression model, a seven-gene signature containing AFAP1L2, CAMK1D, LOXL2, PIK3CG, PLEKHG1, RARRES2, and SPP1 was identified to construct a risk stratification model. The OS and PFS of the high-risk group were significantly worse than that of the low-risk group (P<0.001, P<0.001; respectively). The receiver operating characteristic (ROC) curve analysis confirmed the good potency of the seven-gene signature. Similar findings were validated in two independent cohorts. In addition, the proportion of macrophages M2 and Tregs was higher in high-risk patients (P=0.041, P=0.022; respectively). Conclusion: Our study established and validated a seven-gene signature associated with TME, which might serve as a prognosis stratification tool to predict survival outcomes of advanced LUAD patients. In addition, our research could provide some references of combined immunotherapy in advanced LUAD patients, including induction of macrophages M2 to polarize macrophages M1 and regulation of the function of Tregs immunosuppressive cells.